1998
DOI: 10.2136/sssaj1998.03615995006200040019x
|View full text |Cite
|
Sign up to set email alerts
|

Solute Transport in Seasonal Perched Water Tables in Loess‐Derived Soilscapes

Abstract: Hydraulically restrictive fragipans and argillic horizons are a common feature of loessial soils in the Palouse region of northern Idaho, resulting in perched water development during the winter and early spring. The high relief of the region may result in lateral flow of perched water and solutes. This study was initiated to quantify the rates of solute movement through perched water at three sites receiving 610, 700, and 830 mm of annual precipitation. Three transects, perpendicular to slope contours, consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The eastern Palouse is dominated by hydraulically restrictive layers (argillic or fragipan horizons) that limit the depth of root penetration and generate perched water tables and sub-surface lateral flow (Brooks et al 2012). Across the study site, hydraulically restrictive horizons are found between 0.3 and 1.5 m below the surface, as determined using a 1 650 kg m -3 bulk density threshold to establish presence of a restrictive horizon (Reuter et al 1998). Palouse fields have high spatial variability with short and steep (45-55% slope) northeast facing slopes and longer, more gradual southwest facing slopes (Brooks et al 2012).…”
Section: Site Description and Field Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The eastern Palouse is dominated by hydraulically restrictive layers (argillic or fragipan horizons) that limit the depth of root penetration and generate perched water tables and sub-surface lateral flow (Brooks et al 2012). Across the study site, hydraulically restrictive horizons are found between 0.3 and 1.5 m below the surface, as determined using a 1 650 kg m -3 bulk density threshold to establish presence of a restrictive horizon (Reuter et al 1998). Palouse fields have high spatial variability with short and steep (45-55% slope) northeast facing slopes and longer, more gradual southwest facing slopes (Brooks et al 2012).…”
Section: Site Description and Field Datamentioning
confidence: 99%
“…Step 1) and a 1 650 kg m -3 bulk density threshold to establish presence of a restrictive horizon (Reuter et al 1998). 3.…”
Section: Site Description and Field Datamentioning
confidence: 99%
See 1 more Smart Citation
“…These soils are classified as Fragic Luvisols using the World Reference Base for Soil Resources. Typical soil horizonation consists of an Ap, Bw, E, and a Btxb (fragipan) that occurs at an average depth of 0Ð86 m. These fragipans have low K s (0Ð1 to 1 mm day 1 ), high bulk density (¾1650 kg m 3 ), and relatively high clay content (typically 6 to 8% larger than the overlying soil horizons) (Reuter et al, 1998;McDaniel et al, 2001). Seasonal perched water tables develop above the fragipan from approximately November through to May (McDaniel and Falen, 1994;McDaniel et al, 2001).…”
Section: Site Descriptionmentioning
confidence: 99%
“…At these sections, dye stained the soils horizontally indicating there was lateral flow occurring. Soils closer to the surface are typically higher in soil P concentrations, so lateral movement along the more impenetrable layer could lead to the transport of higher concentrations of nutrients than vertical infiltration deeper in the soil profile (Reuter, McDaniel, Hammel, & Falen, 1998;Walter et al, 2000).…”
Section: Dye Stainingmentioning
confidence: 99%